2019
DOI: 10.1596/978-1-4648-1432-7
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Malnutrition in Ethnic Minority Communities of Vietnam: Issues and Options for Policy and Interventions

Abstract: Books in this series are published to communicate the results of Bank research, analysis, and operational experience with the least possible delay. The extent of language editing varies from book to book. This work is a product of the staff of The World Bank with external contributions. The findings, interpretations, and conclusions expressed in this work do not necessarily reflect the views of The World Bank, its Board of Executive Directors, or the governments they represent. The World Bank does not guarante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 64 publications
3
25
0
Order By: Relevance
“…The indirect effect of SES on U5MR is found through two forms of undernutrition, that is, underweight and stunting. This outcome corroborates the findings of a great deal of the previous works on the effect of SES on nutrition in low and middle‐income countries [4, 21–25] and in Vietnam [7–9].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The indirect effect of SES on U5MR is found through two forms of undernutrition, that is, underweight and stunting. This outcome corroborates the findings of a great deal of the previous works on the effect of SES on nutrition in low and middle‐income countries [4, 21–25] and in Vietnam [7–9].…”
Section: Discussionsupporting
confidence: 90%
“…Mbuya et al . (2019) underscored a number of ethnic minority children who were chronically undernourished and living in lower socio‐economic regions, and socio‐economic disparities were the causes of undernutrition in different regions in Vietnam [9].…”
Section: Introductionmentioning
confidence: 99%
“…This is demonstrated by the malnutrition prevalence in Muong and Tay children from the minor ethnic groups as compared to the more socially and economically advantaged Kinh group. The World Bank Group reported in 2016 that the Kinh and Hoa people (originated from China, a small ethnicity, but living in market-centre areas of Ho Chi Minh City), has the poverty headcount rate only 3.2%, much lower than minor ethnicities (44.6%) [34]. It could be suggested that the nutritional status of Kinh children with a double burden (under and over-nutrition) is typical of a rapidly developing country with a middle-income population, whilst dominance of malnutrition in Muong and Tay more closely resembles low income regions.…”
Section: Discussionmentioning
confidence: 99%
“…Ethnic minority CU5 are greatly affected, having higher rates of stunting (31.4%) and underweight (21%) than ethnic majority Kinh children (15% stunted; 8.5% underweight) [34,38]. The social and economic relevance of undernutrition is evident -ethnic minority groups constitute 14% of the Vietnamese population or about 13.5 million people [34].…”
Section: Introductionmentioning
confidence: 99%
“…However, as Reinhardt and Fanzo [6] remarked about the inclusion of nutrition-sensitive interventions in larger multi-sectoral programs, little is known on how HGSF components contribute to and interact with other interventions in complex NSA programs [32]. Questions regarding bene ts and costs of HGSF programs [32] and their implementation and sustainability in mountainous areas, are yet to be answered.These knowledge gaps and the role of HGSF in addressing undernutrition among CU5 are particularly relevant in the context of countries such as Vietnam, with rapid economic development, but where the signi cant improvements in reducing undernutrition are not distributed equally in the population [34]. In Vietnam, disadvantaged ethnic minority communities in isolated mountainous areas are most affected [35]; their undernutrition is exacerbated by a complex mix of agro-ecological, socio-economic and cultural factors [34,36,37].…”
mentioning
confidence: 99%